Historical characteristics of the Golden Horde city - Marsel Radikovich Nurkhamitov, Leonard Fyodorovich Nedashkovsky, (Opción, 2019)
The article describes the main historical features of the city of the Golden Horde. It shows its specificity in comparison with synchronous urban settlements in various regions of Eurasia via comparative qualitative research methods. As a result, the steppe cities of UlusJuchi had both common features inherent in all medieval cities of Europe and Asia, as well as historical features associated with specific conditions of emergence and subsequent existence. In conclusion, the Golden Horde city, in comparison with other medieval cities, bears in itself features of the general and peculiar.